SEISMIC REFLECTION STUDIES OF THE AMERY ICE SHELF, EAST ANTARCTICA: DELINEATING METEORIC AND MARINE ICE - McMahon K.L.; Lackie M.A. (My University, 2006)
A detailed seismic reflection survey has been performed, utilizing a 24-channel spread with a 10 m geophone spacing, giving a maximum fold coverage of six, with the aim of revealing a detailed view of the subsurface structure of the Amery Ice Shelf, showing meteoric and marine ice thicknesses, water column thickness and sediment structure. The survey has successfully delineated the subhorizontal meteoric and marine ice layers, with average thicknesses of 754 and 20 m, respectively. The water column is 595 m thick, placing the seafloor at a depth of 1369 m below the ice surface. A 55 m thick, subhorizontally layered sedimentary unit can be seen, below which are deep features, at approximately 2225 m below the surface. These features could reveal the presence of dykes, a broken bedrock surface or glaciologically derived clasts that are sufficiently large enough to show up within the data. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: AMERY ICE SHELF; EAST ANTARCTICA; ICE SHELF; MARINE ICE; REFLECTION SEISMOLOGY; REFRACTION SEISMOLOGY